A Case Report: Can Citrin Deficiency Lead to Hepatocellular Carcinoma in Children? - He, Jiayi; Zhang, Jianling; Li, Xuesong; Wang, Hong; Feng, Cui; Fang, Feng; Shu, Sainan (Frontiers in Pediatrics, 2019)
Citrin deficiency initially presents as neonatal intrahepatic cholestasis (NICCD) and often resolves within first year of infancy. Failure to thrive and dyslipidemia caused by citrin deficiency (FTTDCD) has been recently proposed as a novel post-NICCD phenotype and its clinical features are still being established. Herein, we encountered a 2-year-old girl who was hospitalized for intermittent fever lasting 10 days. Besides pneumonia, we observed an NICCD-like phenotype with the presence of liver dysfunction, dyslipidemia, aminoacidemia, organic academia, and extremely high levels of alpha-fetoprotein (AFP). Genetic testing confirmed the diagnosis of citrin deficiency and, liver histology revealed she had already developed cirrhosis. Although, improvement of biochemical parameters and liver histology were observed after treatment that included dietary restrictions and symptomatic treatments, AFP levels remained elevated (>400 ng/ml) during a 3-year follow-up period. Moreover, liver magnetic resonance imaging (MRI) examination performed on the patient at age 5 revealed the development of multiple liver nodules with diffusion restriction on diffusion-weighted imaging (DWI). These observations highly indicate the possibility of hepatocellular carcinoma (HCC). Thus, this case reveals that an NICCD-like phenotype complicated with cirrhosis can exist during FTTDCD stage without any prior signs. It also emphasizes the necessity of monitoring AFP levels during follow-up for citrin deficiency patients with persistently high AFP level after treatment as FTTDCD may progress to HCC. Individualized treatment strategy for patients with FTTDCD also need to be explored.